Pengaruh Kepemimpinan Dan Karakteristik Individu Terhadap Nilai - Nilai Budaya Organisasi Pada Karyawan Di PT. Jamkrindo Cabang Makassar - Sitti Ahyana Juwita; Naidah; Nasrullah (Pusat Riset dan Inovasi Nasional, 2025)
This study is a quantitative study that aims to determine the influence of leadership and individual characteristics on organizational culture values ​​on employees of PT. Jamkrindo Makassar Branch. The sample in this study was all 35 employees, using the total sampling method. Data collection was carried out through questionnaires and analyzed using chi-square statistical tests, logistic regression, and multiple linear regression with the help of SPSS version 26. The results of the study indicate that both leadership and individual characteristics have a significant effect on organizational culture values.This finding emphasizes the importance of strengthening the role of leadership and understanding individual characteristics to improve the internalization of organizational culture in the work environment